A Review of Analytical Methods for Calcium Salts and Cholecalciferol in Dietary Supplements. (19th May 2022) - Santos, Widson Michael dos; de Souza, Myla Lôbo; Nóbrega, Fernanda Pontes; de Sousa, André Luiz Moreira Domingues; De França, Elvis Joacir; Rolim, Larissa Araújo; Rolim Neto, Pedro José
Abstract: Dietary supplements composed by the combination of a calcium salt with cholecalciferol (vitamin D3 ) are widely used for improving bone health in conditions caused by the deficiency of these compounds in the body. Historically, these supplements have been linked to quality and safety issues. In the case of calcium salts, the presence of potentially toxic contaminants such as lead (Pb) has already been alerted by health authorities from different countries. Meanwhile, cholecalciferol is very unstable under inadequate manufacturing and storage conditions. The content of both compounds in commercial dietary supplements is often found to be in disagreement with the label claims, which can lead to a deficient or excessive nutrient intake by consumers. In this scenario, analyzing these compounds is still a difficult and time-consuming task, which usually requires specific pretreatment procedures and multiple analytical methods due to the inorganic nature of calcium and the organic nature of cholecalciferol. Therefore, this article reviews the analytical methods, described in official compendia and scientific literature, for the determination of calcium salts and cholecalciferol in dietary supplement formulations. We also approached the sample preparation procedures highly required due to the matrix complexity of these materials.